USE OF A TWO-STAGE COMBINED SCHEME FOR HEAT EXCHANGERS CONNECTION IN HEATING POINTS FOR HOT WATER SUPPLY OF INSULATED BUILDINGS - Aleksakhin, O.; Boblovskyi, O.; Kruhliakova, O. (Municipal economy of cities. Series: «Economy science», 2024)
The article addresses the features of the functioning of centralised heat supply systems of residential micro-districts considering the improvement of thermal insulation of existing buildings. It also analyses the performance characteristics of hot water supply heaters installed on individual heat points of insulated buildings. The authors compared the heat transfer surface area of heaters and network water flow rate through the heating point for one-stage and two-stage combined schemes of connection of heat exchangers and heat networks. The analysis of calculation results showed that using a two-stage combined connection scheme reduces the consumption of network water through the individual heat supply unit compared to the one-stage scheme. However, the two-stage scheme causes the necessity to increase the heat transfer surface area compared to the one-stage connection scheme. We generalised the results by formulas for calculating water flow rate from distribution heat networks and heat transfer surface area. It is possible to use the obtained results to develop a strategy for reforming micro-district centralised heating systems. Using a two-stage combined connection scheme for hot water supply heat exchangers installed on individual heating points (IHP) of additionally insulated buildings reduces network water consumption through the individual heating point by 8–16% compared to a one-stage connection scheme. The device of a two-stage combined scheme in comparison with a one-stage scheme causes the increase of heat transfer surface area of heat exchangers of the hot water supply of individual heating points from one and a half to two times depending on the accepted design temperature of heating of cold water at the first stage of the heating unit. The results of calculations are approximated by equations, allowing, with acceptable accuracy, to compare the indicators of two-stage combined and one-stage schemes of connection of water heaters for individual heating points of insulated buildings.